Increases in loneliness among Older Americans Act participants during COVID-19 - Menne, Heather L.; Osborne, Jason; Pendergrast, Claire (Frontiers in Public Health, 2024)
Loneliness is increasingly understood as a public health crisis, and older adults are experiencing particularly severe impacts. Social distancing efforts during the COVID-19 pandemic may have increased loneliness among older adults. Guided by the Social Ecological Model, this study uses two cross-sectional waves of the National Survey of Older Americans Act Participants (NSOAAP) from 2019 and 2021 to expand understanding and identify possible points of intervention to increase social support for vulnerable older adults. Results reveal that while home-delivered meal participants have higher levels of loneliness than congregate meal participants, levels of loneliness did not increase during the COVID-19 pandemic and their loneliness levels did not differ significantly by age, geographic location, or living arrangement. Congregate meal participants’ loneliness increased during the first year of the pandemic, particularly for participants aged 65–74, those living in suburban or rural areas, and those living alone. These findings suggest opportunities for policymakers and aging services providers who seek to increase social engagement among older adults who participate in Older Americans Act (OAA) nutrition programs. The evidence suggests a need for increased social engagement initiatives through OAA programs that prioritize social support for groups who are disproportionately burdened by loneliness.